UNDERSTANDING POLITENESS IN COMMUNICATION (World Bulletin of Social Sciences, 2023)
Understanding politeness is cited in the monograph of N. I. Formanovskaya, as well as T. V. Larina. Thus, T. V. Larina writes: "politeness is understood as a nationally specific communicative category, the content of which is communicative behavior (linguistic and non-linguistic) aimed at compliance with socially accepted norms in harmonious, conflict-free communication and interactive communication system of ritualized strategies (establishing, maintaining and ending interpersonal communication)".